Elizabeth Bowen : empire, gender and travel in the Twentieth Century - Keown, Edwina (Trinity College (Dublin, Ireland). School of English, 2006)
‘Elizabeth Bowen: Empire, Gender and Travel in the Twentieth Century’ examines how Elizabeth Bowen (1899-1973) uses travel and transport technologies figuratively throughout her writing to interrogate the historical breaks between pre-World War 1 British imperialism and post-World War 11 British decolonisation. Bowen tracks the changes in British identity and society in the aftermath of the fragmentation of the Empire and the concomitant crises in gender. My focus is firstly on the inter-relation between Bowen’s themes and her travel metaphors; on how her themes and metaphors influence her formal development. My thesis is structured into four thematic chapters, according to Bowen’s examination of the decline of the British Empire and the changing gender roles of her lifetime through the types of vehicular and travel motifs that she uses to investigate these changes. Chapters one, three and four cross-examine the stories and novels that chronicle her contemporary moment and each chapter is divided into three subsections, which are categorised either by a particular travel metaphor or by a novel. Since Chapter two concentrates on her historical writing it is structured separately from the other chapters.
Embargo End Date: 2022-01-01
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin, 2006